2022
DOI: 10.1093/nar/gkac925
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanism of the type I-G CRISPR effector

Abstract: Type I CRISPR systems are the most common CRISPR type found in bacteria. They use a multisubunit effector, guided by crRNA, to detect and bind dsDNA targets, forming an R-loop and recruiting the Cas3 enzyme to facilitate target DNA destruction, thus providing immunity against mobile genetic elements. Subtypes have been classified into families A-G, with type I-G being the least well understood. Here, we report the composition, structure and function of the type I-G Cascade CRISPR effector from Thioalkalivibrio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…Cas3 is universally conserved across all type I CRISPR systems, despite the differences in Cascade composition (7). In the type I-G system Cas3 is an integral subunit of Cascade rather than being recruited on target DNA binding (24,39). This association between Cas3 and Cascade has also been observed in a type I-…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Cas3 is universally conserved across all type I CRISPR systems, despite the differences in Cascade composition (7). In the type I-G system Cas3 is an integral subunit of Cascade rather than being recruited on target DNA binding (24,39). This association between Cas3 and Cascade has also been observed in a type I-…”
Section: Discussionmentioning
confidence: 89%
“…When submitted to a phage P1 challenge assay, cells expressing the K39A or D164A Cas3 variant showed full immunity against phage infection under induced condition, and compromised immunity at higher MOIs compared to wild-type Cas3 when expression was uninduced (Figure 2B). In previous in vitro experiments, we observed that T. sulfidiphilus Cascade in the absence of ATP (and thus helicase activity) only cleaved target DNA at the site of Cas3 loading (39). This appears to be enough in vivo to prevent target plasmid and phage replication as long as the type I-G CRISPR effector is highly expressed or MOI is low.…”
Section: The Importance Of Cas3 Helicase and Nuclease Activities For ...mentioning
confidence: 89%
See 2 more Smart Citations
“…Previously, we reported the structure and mechanism of the type I-G system from Thioalkalivibrio sulfidiphilus [39], demonstrating the constitutive association of Cascade with the Cas3 subunit. Here, we repurpose the T.…”
Section: Introductionmentioning
confidence: 99%